2017
DOI: 10.1108/tr-12-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Edu-tourist’s perceived service quality and perception – the mediating role of satisfaction from foreign students’ perspectives

Abstract: PurposeThe purpose of this paper is to test a conceptual model that takes into account both edu-tourists’ perception and perceived service quality in explaining purchase intention of academic degrees from the foreign universities. Design/methodology/approachThe study is based on an empirical examination with applying multivariate data analysis. The data were collected through survey questionnaires and analysed by using structural equation modelling procedure. FindingsThe survey result discovered that the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…It is believed that students consider service quality in their decision making for selecting a university. This supports that service quality in an educational tourism context is essential, and institutions should take advantage of the competitive nature of absorbing edutourists and evaluating service quality (Rahman, Hassan, Osman-Gani, Abdel Fattah, & Anwar, 2017).…”
Section: Introductionmentioning
confidence: 60%
“…It is believed that students consider service quality in their decision making for selecting a university. This supports that service quality in an educational tourism context is essential, and institutions should take advantage of the competitive nature of absorbing edutourists and evaluating service quality (Rahman, Hassan, Osman-Gani, Abdel Fattah, & Anwar, 2017).…”
Section: Introductionmentioning
confidence: 60%
“…Customer satisfaction is a customer's feelings about the quality of the product/service in accord with their expectation (Parasuraman et al, 1994;Rahman et al, 2017). Therefore, customer satisfaction is an important indicator to determine the success of product/service in the market (Famiyehet al, 2018), leading to enhance customer loyalty (Martín-Consuegra et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the student satisfaction varies in Pakistan across most of the universities, the student expectations towards university facilities are low in Pakistan. Results indicate that the student satisfaction towards university facilities in Malaysia has a direct high impact, whereas the students in Pakistan the university facilities impact is lesser (Rahman et al, 2017) The results indicate that there was a significant difference was found in university facilities provided in Malaysia universities than universities in Pakistan. Malaysian students are more satisfied with the facilities provided by universities.…”
Section: Discussionmentioning
confidence: 83%